MySQLite Sync: Middleware for stored data synchronization in mobile devices and DBMSs - Zaia, Guilherme Palmeira [UNESP]; Messias Correia, Ronaldo Celso [UNESP]; Garcia, Rogerio Eduardo [UNESP]; Olivete Junior, Celso [UNESP]; Ezzatti, P.; Delgado, A. (Ieee, 2014)
Data synchronization is a process of establishing equivalence among two data collections. It is essential to distribute databases and several techniques have been implemented in Database Management Systems (DBMS), but it is not a feature for free use versions. Focusing on mobile computing, applications that perform data synchronization have become increasingly popular. However, due to lack of internet connection, synchronization process requires specific features to take place in an asynchrony way. The MySQLite Sync middleware, presented in this paper, perform data synchronization among databases stored in mobile devices and DBMS. To validate our proposal we adopted metrics based on time and number of primary and foreign keys mapped after synchronization, in order to maintain data integrity. The results obtained are presented and discussed showing positive contributions.
Keywords: Data synchronization; database; mobile devices